Impact of Social Media Use on Sleep Patterns among Adolescents: A Cross-Sectional Study - Muhammad, Shahab; Hassan Iqbal; Ata Ullah; Asif Hanif; Nida Hidayat; Asfia Waseem (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To assess the impact of social media use (SMU) on sleep patterns among adolescents. METHODOLOGY: This analytical cross-sectional study was conducted at the Armed Forces Institute of Mental Health in Rawalpindi from March to September 2024. A total of 380 adolescents aged 10–19 years were selected using a nonprobability consecutive sampling technique after applying inclusion and exclusion criteria. Sociodemographic data and the Pittsburgh Sleep Quality Index (PSQI) were employed to assess SMU and sleep quality at bedtime. Poor sleep quality was indicated by a PSQI global score of > 5. RESULTS: Of the participants, 60% reported using social media, with TikTok being the most frequently used platform (17.4%). The prevalence of poor quality of sleep among participants was 44.2%. Adolescents who used social media for extended hours, particularly in the evening or at night, had significantly higher PSQI scores (p < 0.001). A strong association was found between bedtime social media use and poor sleep quality. Among adolescents with poor sleep quality, 88.1% were social media users compared to 11.9% non-users (p < 0.001). CONCLUSION: This study demonstrates a significant association between SMU patterns and adolescent sleep quality. These findings suggest that increased exposure to social media, especially during critical hours preceding sleep, may adversely affect sleep latency, duration, efficiency, and overall sleep quality.